Studi Eksperimental Kinerja Sistem AC Split Setelah Retrofit Refrigeran R32 dengan R1270 Sebesar 40% (Universitas Islam 45 Bekasi, Fakultas Teknik, Jurusan Teknik Mesin, 2025)
This study analyzes the performance of a 1 PK split-type air conditioner after replacing a less environmentally friendly refrigerant with a more environmentally friendly alternative, namely from R32 to R1270. Tests were conducted with R1270 in a mass of 40%, at variations of evaporator inlet temperatures of 23°C, 25°C, and 27°C, and condenser inlet temperatures of 30°C and 35°C. R1270 showed a 49,59% decrease in cooling capacity compared to R32, due to its lower cooling capability, which resulted in reduced power consumption by the compressor in R1270 which decreased by 42,09% compared to R32. In addition, the COP value of R1270 was 21,48% lower than that of R32. While R32 still exhibits better thermal performance, R1270 offers higher power consumption efficiency, making it a more energy-efficient choice.